Langlands & Bell - Internet giants masters of the universe - Herzog, Hans-Michael 1956-; Vidler, Anthony 1941-2023 (Ikon, 2018)
Celebrating a new body of work by British artists, Ben Langlands and Nikki Bell, marking the 40th year of their artistic partnership. Featuring the new iconic architecture of the global technology companies such as Apple, Facebook and Google, the exhibition includes a new series of relief sculptures, installations, digital animations and portraits that explore the increasingly profound influence they have on our lives in the age of "Big Data". The artist-duo often work from plans and architectural drawings they research online including buildings that are yet to be completed. A new Ikon commission, Google, Charleston East (2018) is a huge model of Google's new global HQ under construction at Mountain View in California. The exhibition also includes a series of portraits of the "Masters of the Universe", founders and CEOs of the Internet Giants including Bill Gates, Mark Zuckerberg, and Steve Jobs appearing as religious icons for the digital age accompanied by their own words. Exhibition: Ikon Gallery, Birmingham, UK (21.03.-10.06.2018)
Ausstellung: 21 March - 10 June 2018, Ikon Gallery, Birmingham
Keywords: Langlands & Bell; Relief; Computerkunst; Installation -- Kunst; Ausstellungskatalog -- Ikon Gallery -- 21.03.2018-10.06.2018 -- Birmingham; Bildband